Implementasi Metode Outdoor Learning dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Alam Ungaran - Anisatul Ummah; Ida Zahara Adibah; Isnaini Isnaini (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This research is motivated by the low level of students’ learning motivation in Islamic Religious Education (PAI), which is still largely dominated by conventional approaches and tends to provide less meaningful learning experiences. This study aims to analyze the implementation of the outdoor learning method and examine its implications for improving students’ learning motivation at Sekolah Alam Ungaran. This research employs a qualitative approach with a descriptive design, with data collected through observation, interviews, and documentation involving teachers, the principal, and students as research subjects. The findings indicate that the learning process is carried out through the concept of Belajar Bersama Alam (BBA), which emphasizes the use of the natural environment as a learning resource integrated with religious values. Activities such as planting plants, rihlah, and observing natural phenomena provide contextual and meaningful learning experiences for students. The improvement in students’ learning motivation is reflected in several indicators, including active participation, enthusiasm during the learning process, direct involvement in activities, the emergence of curiosity through questioning and observation, and persistence in completing tasks. In addition, a more flexible and non-monotonous learning atmosphere supports students’ comfort and engagement. Therefore, the implementation of the outdoor learning method is effective in creating meaningful learning experiences while enhancing students’ learning motivation in the context of PAI learning.